2009
DOI: 10.17660/actahortic.2009.821.10
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Growth and Development of Tomato Crop

Abstract: Crop models are powerful tools to test hypotheses, synthesize and convey knowledge, describe and understand complex systems and compare different scenarios. Models may be used for prediction and planning of production, in decision support systems and control of the greenhouse climate, water supply and nutrient supply. The mechanistic simulation of tomato crop growth and development is described in this paper. The main processes determining yield, growth, development and water and nutrient uptake of a tomato cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 45 publications
1
40
1
11
Order By: Relevance
“…Protected environment models are necessary if one wishes to perform some optimization in production [14]. Although several studies involving the modeling of greenhouse tomato growth can be found [15,16], these models do not consider nutritional relations for the efficient management of mineral nutrition and some are based on variations of mineral concentration in nutrient solution or on drained solution [17].…”
Section: Introductionmentioning
confidence: 99%
“…Protected environment models are necessary if one wishes to perform some optimization in production [14]. Although several studies involving the modeling of greenhouse tomato growth can be found [15,16], these models do not consider nutritional relations for the efficient management of mineral nutrition and some are based on variations of mineral concentration in nutrient solution or on drained solution [17].…”
Section: Introductionmentioning
confidence: 99%
“…Fresh weights of the harvested fruits were recorded weekly. Scenarios were calculated, by using the plant growth model INTKAM (Marcelis et al, 2009), to investigate the contribution of the climate factors to the final production increase. Calculation started by inputting the actual CO 2 concentration, air temperature and VPD of the open greenhouse.…”
Section: Methodsmentioning
confidence: 99%
“…La superficie de referencia corresponde a un cultivo hipotético de pasto con características específicas (Allen et al, 2006;Marcelis et al, 2009).…”
Section: Introductionunclassified
“…The reference surface corresponds to a hypothetical grass crop with specific characteristics (Allen et al, 2006;Marcelis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%